Chlamydia Pneumoniae and Cardiovascular Disease in End-Stage Renal Disease Patients: An Update. (May 2013) - Rassu, M.; Filardo, S.; Mastromarino, P.
Cardiovascular diseases (CVD), due to accelerated atherosclerosis, are responsible for approximately 50% of mortality in End Stage Renal Disease (ESRD) patients undergoing haemodialysis (HD). Over the last decade, Chlamydia pneumoniae, a respiratory pathogen, has been involved in the pathogenesis of atherosclerosis and several reports have suggested the association between C. pneumoniae infection and CVD in HD patients. This report reviews the contribution of C. pneumoniae infection in cardiovascular diseases in ESRD patients, in light of recent studies on cardiovascular risk factors; we hypothesize that C. pneumoniae-infection may contribute to mineral bone disorder and, consequently, vascular calcification. However, further studies are needed to define the relationship between C pneumoniae and bone and vascular disorders in HD patients.